Assessing the Impact of Transit-Oriented Development on Residents’ Quality of Life in Northern Malaysia - Din, Badariah; Abdul Manaf, Halimah; Sabar, Rohafiz; Anuar, Nur Khairiel; Osman, Azim Azuan (Malaysian Institute of Planners, 2023)
Transit-Oriented Development (TOD) is gaining wide acceptance by many state’s governments in Malaysia due to its potential to create a liveable neighbourhood with enhanced mobility. Therefore, this study aims to assess the impact of TOD on the residents’ quality of life in Malaysia northern states. The data for this study were gathered from a survey on 360 residents who used the Northern KTM commuter train service. Descriptive and inferential statistics including chi-square test and PLS-SEM technique was performed to analyse the data and produce the findings. The findings of this study shown that there were significant differences in travel behaviour patterns (companions, frequencies, and walking durations) with respect to respondents’ travel purposes. Moreover, it was revealed that land-use diversity and walkable design as important TOD principles that contribute to their quality of life. The findings of this research would serve as a base but critical information to direct future National Estate Development Plan.